Game-based Islamic ethics for Palestine awareness: A narrative review and conceptual framework - Alvi Muyasiroh Khoironi Zulkarnaen; Ghefira Aleyda Nova (Islamic perspective on Communication and Psychology, 2025)
Background: This narrative review examines how Islamic ethical principles rahmah (compassion), ukhuwah (solidarity), and ’adl (justice) can be integrated into immersive game-based learning to strengthen humanitarian awareness and empathy toward the Palestinian crisis among Muslim youth. Despite the widespread circulation of digital information, many young people remain emotionally distant from the lived realities of Palestinians, indicating a gap between awareness and ethical action.  Methods: This narrative review examines how Islamic ethical principles rahmah (compassion), ukhuwah (solidarity), and ’adl (justice) can be integrated into immersive game-based learning to strengthen humanitarian awareness and empathy toward the Palestinian crisis among Muslim youth. Despite the widespread circulation of digital information, many young people remain emotionally distant from the lived realities of Palestinians, indicating a gap between awareness and ethical action.  Findings: The findings indicate that game-based interventions grounded in Islamic ethics have significant potential to strengthen cognitive and emotional engagement with humanitarian issues. Conclusion: This approach can bridge the gap between digital consumption and ethical action, encouraging youth to transition from passive awareness to active solidarity.  Novelty/Originality of this article: The conceptual framework developed in this review offers a novel pathway for integrating religious values, digital technology, and humanitarian advocacy into a unified educational tool.